Community Resilience during the COVID 19 Pandemic: Experiences of Community-Based Violence Prevention and Recidivism Reduction Program Administrators - Alderden, Megan (American journal of criminal justice, 2023)
Community-based agencies play a notable role in local violence prevention and reentry services in the United States. The COVID-19 pandemic and governmental responses to contain its spread fundamentally transformed the day-to-day lives of most individuals and the workplace. This study examined the challenges experienced and adaptations employed by community-based organizations as they navigated shelter-in-place orders and other workplace and community restrictions. Between July and September of 2020, researchers completed 16 semi-structured interviews with agency administrators of community-based organizations serving at-risk youth or formerly incarcerated persons operating in a large Midwestern city. The findings highlight several challenges faced by agency administrators as they attempted to maintain services to their clients, including having to move from largely in-person service modalities to methods of contact and communication that embraced social distancing and virtual interaction. They also actively responded to the health safety needs of their staff, clients, and community by instituting new safety protocols, like staff and client COVID-19 testing, handing out personal protection equipment and supplies, and educating community members. The findings demonstrate a high degree of community mobilization and resilience in light of a global crisis.